ORGANIZATION OF CHILDREN OPPORTUNE VACCINATION OF ARRIVING IN KRASNODAR REGION - O.K. Aleksandrova ("Paediatrician" Publishers LLC, 2008)
The number of vacationists on resorts of Krasnodar region exceeded 12 million in 2007 year. More then 500 thousands of vacationists were children in organized groups. Because of well coordinated work of hygiene and disease prevention and pediatric services of region the number of cases of pertussis, measles, rubella, epidemic parotiditis, hepatitis A and B and other infectious diseases, dirigible with specific prophylactic measures, was greatly decreased. The opportunity of vaccinal prevention of varicella appears by 2008 year. It's advisable to make a hepatitis a vaccination of children, arriving from endemic regions, domiciliary. «Delivered» cases of disease cause significant economical damage to the budget of public health service of Krasnodar region. Preliminary planning of a journey and assumption of prophylactic measures can greatly decrease the risk of negative influence of trip on child's health.Key words: children, vaccination, prophylaxis, infectious disease.